PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS INFORMASI PELAPORAN KEUANGAN (Studi Pada SKPK di Kota Langsa) - Andre Revaldo; Nasrul Kahfi Lubis; Afrah Junita (Jurnal Mahasiswa Akuntansi Samudra, 2021)
This study aims to determine the effect of applying government accounting standards, information technology and internal control to the quality of financial reporting information in SKPK in Langsa City. The method used in this study is a quantitative method using the help of SPSS 24. The population in this study were all 30 SKPK in Langsa City. Methods of data collection by distributing questionnaires and by using measuring tools in the form of validity and reliability tests. The analytical method used is multiple linear regression analysis using hypothesis testing, namely t test and F test. The results of the t test show that (1) the application of government accounting standards has a significant effect on the quality of financial reporting information, (2) information technology has a significant effect on the quality of financial reporting information, (3) Internal control has no significant effect on the quality of financial reporting information. The results of the F test show that the application of government accounting standards, information technology and internal control simultaneously has a significant effect on the quality of financial reporting information.